Formation of communicative competence in future teachers of physical education - Tokpanov, Alibek; Stukalenko, Nina (Pedagogy and Psychology, 2021)
The article presents the generalized results of research on the formation of communicative competence of future physical culture teachers in the conditions of professional training at a higher education institution. The scientific-methodological and methodological aspects of the process under study, the theoretical and practical significance of its results are disclosed. As a result of the study, it was found that if the professional training of future physical education teachers is organized using a communicative approach, then modern communicative teaching methods are aimed at the formation of their communicative competence within the educational process of the university on the basis of the elective course "Communication and physical culture" and appropriate educational and methodological support, this will help to increase the level of their communicative competence.